Boronic acid-modified poly(amidoamine) dendrimers as sugar-sensing materials in water. Issue 18 (14th March 2016) - Liang, X.; Bonizzoni, M.
Abstract : High-affinity carbohydrate receptors were developed by appending boronic acids to the surface of PAMAM dendrimers. These multivalent hosts were used to discriminate simple sugars in neat water using pattern recognition and optical spectroscopy techniques. Abstract : Boronic acids can be used as receptors in chemical sensors for sugars, but their binding affinity and solubility are usually very poor in water. We improved these parameters by covalently connecting boronic acid moieties to the surface of third-generation poly(amido)amine (PAMAM) dendrimers to form a family of PAMAM–boronic acid receptors that display multivalent behavior. We confirmed the increased interaction strength of these modified boronic acid receptors using diol-containing dyes such as 4-methylesculetin and alizarin red S as probes in optical spectroscopy experiments. We then translated these results to sugar sensing using the self-assembled [PAMAM-ba·(dye) n ] complexes as sensors in an indicator displacement assay. Our approach successfully detected simple sugars ( e.g. fructose, glucose, galactose and ribose) in water, traditionally a very challenging medium for carbohydrate detection. Finally, we demonstrated the use of these polymer-based sensors in a multivariate array sensing platform for the discrimination of simple sugars in water as a proof of principle towards their broader applicability under physiologically and environmentally relevant conditions.